Social media users' online behavior with regard to the circulation of hate speech - Megersa, Tadesse; Minaye, Abebaw (Frontiers in Communication, 2023)
Online hate speech is ripping Ethiopian society apart and threatening the values of democracy, human dignity, and peaceful coexistence. The current study argues that understanding people's responses to hateful posts helps combat hate speech online. Therefore, this study aims to comprehend the roles social media users play in responding to online hate speech. To this end, 14 ethnic-based hate speech posts each with more than 1000 comments were collected from the public space of four purposefully selected YouTube news channels and four Facebook accounts, which are considered as hot spots for the circulation of hate speech during data collection period.Then, 100 random comments were collected from each hate speech post using ‗exportcomment.com' which automatically extract comments from social media posts in excel format. After extracting a total of 1400 random comments, 460 of them were removed because they were found irrelevant and unclear to be coded and analyzed. Then, inductive coding was employed to identify, refine, and name codes and themes that describe the main roles played by social media users in reacting to the hate speeches. The findings showed five major roles social media users play in responding to hatful contents: trolling, pace-making, peace-making, informing, and guarding. The paper discusses the findings and provides recommendations deemed necessary to counter online hate speeches.